Environmental Effects of Bio-Waste Recycling on Industrial Circular Economy and Eco-Sustainability - Sasmoko; Khalid Zaman; Maida Malik; Usama Awan; Wiwik Handayani; Mohd Khata Jabor; Muhammad Asif (Recycling, 2022)
Few prior studies have examined the social and environmental consequences of waste generation and recycling, resulting in a policy gap in the sustainability agenda. The research filled a knowledge vacuum in the literature by investigating the environmental repercussions of different waste generation and recycling processes in the Chinese economy. The study analyzed waste production and recycling statistics over the last 46 years, from 1975 to 2020, and their impact on the nation’s emissions per capita. This study used four primary approaches to determine the links between the examined variables, beginning with the unit root test, which identifies the stationary process of the variables’ underlying processes. Second, the autoregressive distributed lag (ARDL) model was used to produce the variables’ short- and long-run estimates. Third, estimations of Granger causality examined the causal relationships between the variables. Finally, innovation accounting matrices (IAM)were utilized to predict the relationships between variables during the following decade. The unit root estimates imply the mix order of variable integration; hence, it is appropriate to employ ARDL modeling for parameter estimations. The ARDL estimations demonstrate that combustible renewables and waste decrease a nation’s carbon emissions by boosting industrial waste recycling. Despite recycling systems, carbon emissions have escalated to uncontrolled levels owing to the massive production of municipal solid garbage. Sustainable waste management and recycling are vital to reducing carbon emissions. Granger’s estimations of causation imply that combustible renewables and waste and carbon emissions cause industrial and municipal solid waste recycling. Additionally, population growth is responsible for greenhouse gas emissions, biowaste recycling, and industrial waste recycling. Furthermore, this shows the two-way connections between combustible renewables and waste and carbon emissions, implying the need to develop green waste recycling strategies in a nation. The IAM method identified future relationships between variables, which aids policymakers in implementing sustainable waste management practices for a nation. This study concludes that the environmental consequences of waste generation and recycling impede the nation’s circular economy agenda, which can be sustained by knowledge spillovers, chemical reduction in manufacturing, and allocating a certain amount of US dollars to ecological resource conservation.